Pembinaan Wanita Melalui PT.P2W-KSS dalam Membentuk Sikap Wanita (Suatu Studi Evaluatif di Kelurahan Medan Tenggara) - Elviana Safitri; Agus Suriadi; Mia Aulina Lubis (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
This research aims to determine the attitudes of women towards coaching through the integrated program called "Program Terpadu Peningkatan Peranan Wanita Menuju Keluarga Sehat Sejahtera" (PT.P2W-KSS) and to answer the question of whether there is a difference in attitudes between women who are coached through the PT.P2W-KSS program and women who are not coached through the program in Medan Tenggara. The research in in form of quasi-experimental which developed into the comparative technique with an evaluative design that is ex post facto or impact evaluation. The sample in this research is divided into two groups, 45 women respondents who received the coaching through PT.P2W-KSS as the experimental group and other 45 women respondents who did not received the program as the control group. Data analysis techniques and hypothesis testing proposed in this study used non-parametric statistics through the Mann-Whitney test. The determination of this formula is based on the idea that research data includes measurements on an ordinal scale. From the results of the Mann Whitney test with a significance level of 95%, it was found that among the 5 aspects tested the result of Ho was rejected, which means there is a difference in attitudes between women who are coached with women who are not coached through PT.P2W-KSS. This difference reflects the achievement of the program's goal to change women's attitudes. This also affects the ability of women to carry out various roles in the family and community environment optimally.